Sebaceous carcinoma of the vulva: a clinical case and a literature review - V. V. Saevets; A. Yu. Shamanova; N. K. Kuzmin; L. V. Yarina (Malignant tumours, 2026)
Background. Vulvar cancer (VC) is a rare malignancy in women, accounting for no more than 4 % of all cancers. Sebaceous histologic subtypes of VC are exceptionally uncommon. We summarize our own experience and that of other authors regarding presentation, diagnosis, and management. Objective. To present a clinical case of vulvar sebaceous carcinoma and synthesize the available literature to clarify the clinicopathologic features, diagnostics, treatment, and prognosis of this malignancy. Materials and Methods. We described a clinical case of vulvar sebaceous carcinoma treated at our center. In addition, we conducted a systematic literature review (PubMed, MEDLINE, Cochrane Library, eLibrary.ru; 1970–2025; keywords “sebaceous carcinoma”, “vulvar cancer”) of published cases. Results. Immunohistochemistry confirmed sebaceous carcinoma (EMA+, pan-CK+, S100 / Melan-A–); stage IB (pT1bN0M0). A hemivulvectomy achieved a clear margin ≥ 10 mm; no adjuvant therapy was given; at 21‑month follow-up there was no recurrence. The literature review of 16 cases showed that the vast majority of patients (~ 80 %) underwent surgical treatment; inguinal lymph-node metastases were reported in ~ 20 %, and distant metastases in < 10 %. In isolated reports, adjuvant radiotherapy and immunotherapy (PD-1 inhibitors) were used for advanced disease. Conclusion . Vulvar sebaceous carcinoma is exceedingly rare and insufficiently studied, requiring an individualized, multidisciplinary approach. In localized stages, radical surgical excision provides a favorable prognosis. Regional lymph-node assessment is preferably performed via sentinel lymph-node biopsy, and all patients should undergo immunohistochemical evaluation of the mismatch-repair (MMR) system to exclude Muir — Torre syndrome and to determine eligibility for targeted and / or immunotherapy.